Farmers' willingness to participate in a big data platform. Issue 1 (12th September 2019) - Turland, Madeline; Slade, Peter
Abstract: This paper uses a hypothetical choice experiment to examine farmers' willingness to share their farm data with a big data platform. We found that, on average, 36% of farmers are willing to join such a platform. Participation is affected by the characteristics of both the platform and the farmer. The organization operating the big data platform is particularly important: farmers are most willing to share their data with university researchers and least willing to share their data with government. Not surprisingly, farmers with strong privacy preferences are less likely to join a big data platform. However, we found that relatively small financial and nonfinancial benefits significantly increased participation, even among farmers who stated strong privacy preferences. [EconLit classifications: Q12, Q16, Q18]